2012
DOI: 10.1002/adhm.201200140
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Glass Foam Scaffolds are Remodelled by Osteoclasts and Support the Formation of Mineralized Matrix and Vascular Networks In Vitro

Abstract: Remodelling of scaffolds and new bone formation is critical for effective bone regeneration. Herein is reported the first demonstration of resorption pits due to osteoclast activity on the surface of sol-gel bioactive glass foam scaffolds. Bioactive glass foam scaffolds are known to have osteogenic potential and suitable pore networks for bone regeneration. Degradation of the scaffolds is known to be initially solution mediated, but for effective bone regeneration, remodelling of the scaffold by osteoclasts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 43 publications
2
43
0
1
Order By: Relevance
“…5.6 m 2 g À1 compared to 0.15 m 2 g À1 for 45S5 particles [37] in a similar particle size range to those used by Oonishi [36]) and dissolution rate for bone remodelling. Ripamonti et al [38] showed that concave pores could encourage more rapid osteogenesis and osteoclast remodelling of bioactive glasses has been observed in vitro [39]. Further experiments are required to verify this hypothesis, using histology and quantitative methods.…”
Section: In Vivo Studymentioning
confidence: 99%
“…5.6 m 2 g À1 compared to 0.15 m 2 g À1 for 45S5 particles [37] in a similar particle size range to those used by Oonishi [36]) and dissolution rate for bone remodelling. Ripamonti et al [38] showed that concave pores could encourage more rapid osteogenesis and osteoclast remodelling of bioactive glasses has been observed in vitro [39]. Further experiments are required to verify this hypothesis, using histology and quantitative methods.…”
Section: In Vivo Studymentioning
confidence: 99%
“…The objectives of this paper were to: i) Revisit the original Stöber process to provide a comprehensive understanding of how to reliably control particle size, whilst maintaining monodispersed particles; ii) Investigate the subsequent incorporation of calcium with complete quantitative characterisation of the nanoparticles to prove the incorporation of calcium, with the 70S30C composition (70 mol% SiO2, 30 mol% CaO) [32][33][34] as the target value; iii) Assess the dissolution of the particles in artificial lysosomal fluid (ALF) and Simulated Body Fluid (SBF) to determine how they might degrade in the body.…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin was used in this system as it is a hydrolysed form of collagen which is recognisable and adhered to by many cell types [22]. And silica is well documented in biocompatible applications [23][24][25]. Consequently silica-gelatin hybrids also display excellent cell compatibility in vitro with mesenchymal stem cells [9].…”
Section: Introductionmentioning
confidence: 99%